A Blockchain-Based Welfare Distribution Model for Digital Inclusivity - Tartan, Chloe (REGION, 2023)
An unprecedented rate of technological advancement, compounded by the COVID-19 pandemic, has expedited our transition to a fully digitalised society. Traditionally, digital inclusion focuses on an individual’s ability to connect to and access information from the internet. The adoption of novel technologies such as artificial intelligence and blockchain is little distinguished in the literature from internet accessibility. While these digital solutions present novel opportunities, they may also perpetuate or exacerbate the existing hurdles faced by digitally excluded localities. However, these technologies could also be used to tackle the digital divide. Inspired by the design of Bitcoin, the current study offers a conceptual blockchain-based welfare model that adopts a two-pronged approach to enable the fair distribution of capital and resource allocation across the UK regions. The model offers transparency over institutional processes and improves their trustworthiness while preserving privacy. At the community level, the model assumes the application of economic incentives in order to promote digital inclusivity and stimulate cooperation and competition within local cultures. By mobilising both public institutions and communities, such a holistic model would assist the flow of information between the supply and demand side of the regional economy. This approach may not only help to dissolve the welfare losses arising from the digital divide, but also improve social well-being in all regions.